Development Of Machine Learning Algorithms For Fraud Detection In Digital Transactions - Tarigan, Heskyel Pranata (Jurnal Komputer Indonesia, 2024)
This article discusses the development of machine learning algorithms to detect fraud in digital transactions. With the increasing use of online transactions, fraud detection becomes crucial to maintain security. The proposed algorithm uses deep learning techniques to identify anomalous patterns in transaction data. The results show that the algorithm is able to improve the accuracy of fraud detection compared to conventional methods.